The Effect of Online Customer Reviews and Price on Purchase Decisions through Customer Satisfaction as a Mediating Variable for Mie Uda Bro Products in Padang (A Study of the Padang City Community) - Anggi Saputra; Suci Alifah Rahmandani; Annisa Sri Budiman; Susi Evanita; Vidyarini Dwita (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
This causal study aims to analyze the influence of online customer reviews and price on purchase decisions through customer satisfaction as a mediating variable for Mie Uda Bro products in Padang City (A Study of the Padang City Community) to determine the extent to which exogenous variables influence endogenous variables. The population in this study consists of residents of Padang City who have made purchases and viewed online reviews of Mie Uda Bro products in Padang City. The sample size was determined to be 100 samples using the Chocran formula with purposive sampling, a type of non-probability sampling. The data used is primary data obtained through the distribution of questionnaires to the residents of Padang City based on predetermined criteria. The analysis method used is SEM analysis using the SmartPLS 4.0 software. The results of the study indicate that: 1) online customer reviews have a positive and significant effect on purchase decisions, 2) price has a positive and significant effect on purchase decisions, 3) online customer reviews have a positive and significant effect on customer satisfaction, 4) price has a negative and significant effect on customer satisfaction, 5) customer satisfaction does not have a positive and significant effect on purchase decisions, 6) customer satisfaction does not mediate the relationship between online customer reviews and purchase decisions, 7) customer satisfaction does not mediate the relationship between price and purchase decisions